Web data management practices emerging techniques and technologies - Vakali, Athena; Pallis, George (Idea Group Publishing, 2007)
"This book provides an understanding of major issues, current practices and the main ideas in the field of Web data management, helping readers to identify current and emerging issues, as well as future trends. The most important aspects are discussed: Web data mining, content management on the Web, Web applications and Web services" - Provided by publisher
Keywords: Data Mining; Management; Aufsatzsammlung